New approach of (G'/G)-expansion method for RLW equation - Naher, Hasibun; Abdullah, Farah Aini (© 2014 Maxwell Science Publications, 2016)
This article was published in the Research Journal of Applied Sciences, Engineering and Technology [©2014 Maxwell Science Publications] and the Journal's website is at: http://maxwellsci.com/print/rjaset/v7-4864-4871.pdf